Strategies for Energy and Climate Management at the British Columbia Institute of Technology - Moore, Jennie (Journal of Sustainability Perspectives, 2021)
The British Columbia Institute of Technology (BCIT) is Canada's premier polytechnic. In 2008, BCIT partnered with its local electricity utility to hire a full-time energy manager. The following year, BCIT's School of Construction and the Environment initiated a campus-as-living-lab of sustainability project called Factor Four in the seven buildings it occupies on BCIT's main campus in Burnaby. The purpose was to explore whether a four-fold (75%) reduction in materials and energy use could be achieved without compromising service levels. By 2016, the project achieved a 50% reduction in energy use and associated greenhouse gas emissions. Factor Four attracted over four million dollars in funding, engaged over 250 students from 12 educational programs, and produced over $200,000 savings annually. In 2017, BCIT set an ambitious target to reduce its annual greenhouse gas emissions 33% below 2007 levels by 2023, and 80% by 2050, across all five of its campuses. BCIT’s ultimate goal is to become both greenhouse gas neutral and a net energy producer. By setting ambitious targets and systematically implementing energy efficiency improvements, utilizing waste-heat exchange, fuel switching, and developing on-site renewable energy, BCIT is on track to achieving its energy management and climate change goals.